Phosphorus mobilization and localisation in the roots and nodules of a Cape Floristic Region legume, and its impact on nitrogen fixation - Vardien, Waafeka (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.